(untitled) (Archives of Clinical and Medical Case Reports, 2021)
We describe a young female patient with schistosomiasis, HIV and posterior reversible encephalopathy syndrome (PRES) from a South African township. There are overlapping pathophysiological molecular mechanisms between schistosomiasis and PRES and yet no previous descriptions linking the two conditions. This presentation highlights the need for further investigation of this possible link. It also serves to emphasize the need for an updated geographical distribution map of schistosomiasis in South Africa. The interplay between HIV and schistosomiasis continues to be an important study subject in endemic areas.